Hochgebirgstourismus in der Sowjetunion: Entwicklung, Formen und Probleme am Beispiel des Großen Kaukasus - Stadelbauer, Jörg (ERDKUNDE, 1983)
In the former Russian Empire and in the Soviet Union, tourist access to the high mountains began later than in the European Alps. Up to now, tourism has been concentrated on a few dominant centres, above all on the northern slope of the Western and Central Great Caucasus. Most of the tourist settlements in the high valleys are functionally connected with health resorts of the North Caucasian Foreland or the Black Sea coast. Two of the most prominent centres of actual high mountain tourism in the Great Caucasus are examined in more detail; Dombay in the upper Teberda valley and the Pri-el'brus'ye region in the upper Baskan valley. Summer trecking prevails as the most important tourist actitivity over winter skiing. For both centres, expansion plans have been established which strive for 1,700 and 4,000 places respectively. But new conflicts have occurred with the aims of conservation. The region of Teberda-Dombay is defined as a natural reserve, but initial landscape damage is becoming evident. In the upper Baksan valley and the Ebrus region, the ecosystems are still weaker but they also show symptoms of anthropogenic stress. Thus, both examples demonstrate the ecological problems of high mountain tourism. It is necessary to observe the restrictive conditions of conservation laws if it is planned to maintain the scenic resources of these areas which play a dominant role in the Soviet recreational system.